Sosialisasi Perkembangan Bahasa dan Implementasi Budaya Literasi Sejak Dini di SD Cordova Samarinda: Pengabdian - Nur, Nurul Hikmah; Eka Selvi Handayani; Gamar Al Haddar; Muhammad Ibnu Sa’ad; Intan Nur Safikah; Nur Yanti (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The activity "Socialization of Language Development and Implementation of Early Literacy Culture in Cordova Samarinda" generally aims to find out the Socialization of Language Development and Implementation of Early Literacy Culture for Class Teachers and Students of Grade IV SD Cordova Samarinda. The method of implementing this service is by means of surveys and direct socialization in the field. Introduction to language development and getting used to literacy culture from an early age can be started by communicating with people in the home environment, community environment, school environment, by reading story books or fairy tales to children routinely by parents at home and teachers can also implement reading books and students listening in class. Although it seems like a simple activity, reading books to children is the first stage of introducing children to the world of literacy. Improving literacy culture in the digital era, for example, is very important. Literacy has a big role in training children's basic skills in reading, writing and telling stories.